Metabolic Syndrome in Children and Adolescents Living with HIV. Issue 6 (June 2016) - Espiau, María; Yeste, Diego; Noguera-Julian, Antoni; González-Tomé, María I.; Falcón-Neyra, Lola; Gavilán, César; Navarro-Gómez, María L.; Mellado-Peña, María J.; Gracia-Casanova, Mercedes; Colino-Gil, María E.; Méndez, Maria; Ciria Calavia, Luis M.; et al.
Abstract : Background: Metabolic syndrome (MetS) is considered an independent risk factor for developing cardiovascular disease. It is well known that the prevalence of metabolic disorders have increased in pediatric HIV-infected children. The objective of this study is to assess the prevalence and characteristics of MetS in HIV-infected children and adolescents in Spain. Methods: A cross-sectional multicenter study in 152 patients from the pediatric cohort of the Spanish AIDS Research Network (CoRISpe) was performed. MetS was defined according to the new International Diabetes Federation (IDF) diagnostic criteria and the modified National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. Measurements included anthropometry, waist circumference, blood pressure, fasting lipids, glucose and insulin and lipodystrophy assessment. Demographic, clinical, immunological, virological and antiretroviral therapy data were obtained from the Network database. Results: An abnormally low high-density lipoprotein-cholesterol level was the most prevalent disturbance (21.05%) found. Three patients met IDF criteria for MetS (1.97%), and MetS was significantly associated with lipohypertrophy ( P =0.029) in the analysis. When the modified NCEP-ATP III criteria were used, the prevalence of MetS was 5.92% (9 patients), and MetS was significantly associated with Tanner stage ≥2 ( P =0.041), lipohypertrophy ( P =0.001) and higher Z scores for weight and body mass index ( P =0.002 and P <0.001). Insulin resistance was observed in 17 patients (11.18%) and was associated with MetS (as per the modified NCEP-ATP III criteria) ( P =0.03) and lower high-density lipoprotein-cholesterol values ( P =0.036). Conclusions: The prevalence of MetS in our cohort was 1.97% or 5.92%, depending on the diagnostic criteria used. MetS should be actively assessed, particularly in children who show lipohypertrophy.